2002
DOI: 10.1002/lsm.10087
|View full text |Cite
|
Sign up to set email alerts
|

Oral bacteria in multi‐species biofilms can be killed by red light in the presence of toluidine blue

Abstract: Substantial numbers of oral bacteria in multi-species biofilms can be killed by light in the presence of TBO. This may be useful in the treatment of dental plaque-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
77
0
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 14 publications
16
77
0
12
Order By: Relevance
“…The smaller curcumin concentration (0.75 g/L) was sufficient to kill 97.5 % of the microorganisms. Similar results have been shown in previous studies using different PSs on oral bacteria in a biofilm condition [11,13,14,33] Conversely, when PDT was applied to microorganisms in dentine carious lesions, results showed that bacteria were more resistant to PDT within decayed dentine. Furthermore, the phototoxic effect was found to be dependent upon curcumin concentration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The smaller curcumin concentration (0.75 g/L) was sufficient to kill 97.5 % of the microorganisms. Similar results have been shown in previous studies using different PSs on oral bacteria in a biofilm condition [11,13,14,33] Conversely, when PDT was applied to microorganisms in dentine carious lesions, results showed that bacteria were more resistant to PDT within decayed dentine. Furthermore, the phototoxic effect was found to be dependent upon curcumin concentration.…”
Section: Discussionsupporting
confidence: 90%
“…By irradiation with light in the visible range of the spectrum, the PS is excited to its triplet state, and the energy is transferred to the molecular oxygen. Highly reactive singlet oxygen capable of reacting with and destroying biological systems is formed [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This can be addressed partially through the use of polylysine-based cationic photosensitizers, which are currently being studied. 79 …”
Section: Photodynamic Approaches To Biofilm Managementmentioning
confidence: 99%
“…Highly reactive singlet oxygen capable of reacting with biological systems and destroying them is formed. 22,23 PDT represents an alternative antibacterial, antifungal, and antiviral treatment for drug-resistant organisms. [24][25][26][27][28] It is not likely that bacteria would develop a resistance to the cytotoxic action of singlet oxygen or free radicals.…”
mentioning
confidence: 99%